A Sense of the Self from the Margins: Theorizing Adivasi Experience in Kerala - Jobin Thomas (Lapis Lazuli -An International Literary Journal (LLILJ), 2014)
A socio-literary theory achieves coherence by running a complex abstraction of human experiences through a philosophical prism. Its internal consistency is derived both from the universal legitimacy bestowed by its audience, as well as the mathematical precision of its logic. Critical Theory, with its foundational claims to an emancipatory politics, thus derives part of its legitimacy from its promises of a moral and ethical future. Here, the plurality of experiences disrupts the objective and distanced abstraction with an invested, particular engagement. The context of this paper is provided by a battle over the right to represent/mediate political modernity in Kerala. I focus on two Adivasi self-representations which challenge the identity strait-jackets projected on to the Adivasis and attempt to refashion and recreate their identities, politically as well as culturally, on the basis of their lived experience.